Rancang Bangun Sistem Informasi Keuangan Masjid Al – Hikmah Pada PT. Surya Toto Indonesia Berbasis Web - Nasrullah, Irfan; Wicaksono, Imam Amarullah; Taufiq, Rohmat (ITB Ahmad Dahlan Jakarta, 2021)
Al-Hikmah Mosque is located in PT. Surya Toto Indonesia Jl. MH. Thamrin Km. 7 (Serpong) Tangerang Banten Indonesia. Al-Hikmah Mosque is one of the mosques that have many activities, such as routine studies, thematic studies, infaq management, and activities to celebrate Muslim holidays (Eid al-Fitr, Eid al-Adha, and Friday prayers). This study aimed to promote the management of the Al-Hikmah mosque in the management of mosque finances. To support this research, an Al-Hikmah financial information system created that can be used for the purpose of this research. The method of developing the Al-Hikmah mosque information system used the Waterfall method, began from needs analysis with data collection through interview and observation methods, and then precedes with system architecture design and implementation through programming, to the testing phase. This testing phase used the Black Box method and evaluation to test whether the system was running well. The Al-Hikmah Mosque information system hoped that will make it easier for mosque administrators to manage infaq.